Antibacterial Activity of 70% Ethanol Extract of Red Hanjuang (Cordyline fruticosa L.) Leaves Against Staphylococcus aureus - Nurviana, Vera; Faridah, Ida; Zustika, Diana Sri (Tropical Biopharmaca Research Center, IPB University, 2025)
Productive cough is a common symptom of bacterial respiratory infections. Red hanjuang (Cordyline fruticosa L.) leaves have been traditionally used to relieve such conditions. This study aimed to standardize red hanjuang leaf plant material and evaluate the antibacterial activity of its 70% ethanol extract against Staphylococcus aureus. Phytochemical screening revealed the presence of flavonoids, saponins, tannins, polyphenols, quinones, steroids, monoterpenoids, and sesquiterpenoids. Antibacterial activity was tested using the well diffusion method at concentrations of 10%, 25%, 35%, and 50%, with minimum inhibitory concentration (MIC) tests ranging from 10% to 0.8%. Specific and non-specific standardization showed water-soluble extract at 34.593%, ethanol-soluble extract at 31.663%, moisture content at 4.67%, drying loss at 9.57%, total ash content at 7.70%, and acid-insoluble ash at 0.89%. The extract demonstrated strong antibacterial activity at all tested concentrations. The lowest active concentration was 10%, with an MIC value at 8%, forming an inhibition zone of 2.43 mm. These findings support the potential of red hanjuang leaves as an herbal antibacterial agent.